Multi-Frequency Aeroelastic ROM for Transonic Compressors - Marco Casoni; Andrea Magrini; Ernesto Benini (Aerospace)
The accurate prediction of the aeroelastic behavior of turbomachinery for aircraft propulsion poses a difficult yet fundamental challenge, since modern aircraft engines tend to adopt increasingly slender blades to achieve a higher aerodynamic efficiency, incurring an increased aeroelastic interaction as a drawback. In the present work, we present a reduced order model for flutter prediction in axial compressors. The model exploits the aerodynamic influence coefficients technique with the adoption of a broadband frequency signal to compute the aerodynamic damping for multiple reduced frequencies using a single training simulation. The normalized aerodynamic work is computed for a single oscillation mode at three different vibration frequencies, comparing the outputs of aerodynamic input/output models trained with a chirp signal to those from single-frequency harmonic simulations. The results demonstrate the ability of the adopted model to accurately and efficiently reproduce the aerodynamic damping at multiple frequencies and arbitrary nodal diameters with a single simulation.